Photodegradation extraction of Alpinia galangal with magnesium oxide for solar energy application / Auni Kiasatina Azman - Azman, Auni Kiasatina (2023)
After decades of study and development, a few solar energy applications, such as photovoltaic and photothermal, emerged that helped people, particularly in the area of power. This was due to the research on solar energy utilization. The major goal of this study was to evaluate the possibility of selective metal oxide and organic dye for solar energy applications in the preliminary stages. The process occur was photocatalytic degradation, which was investigated by using the organic dye that was extracted from an Alpinia galangal plant using the part of leaves, under the UV light within 2,4,6 days in the presence of metal oxides magnesium oxide (MgO), which act as photocatalysts to speed up the rate of degradation and to examine the potential of the organic dye before and after being exposed to sunlight. As the result the colour of the organic dye will change from green to orange colour and its conductivity will increase as the temperature of the organic dye under sunlight increase to prove that the degradation its occur and potentially. In conclusion, this process was one of the preliminary stages for knowing the ability of the organic dye on using for the next stage for generating electricity by absorbing light from the sunlight that are suitable for generate low current electricity.